REGISTRATION APPLICATION AND EXAM SIGN IN BAHASA PARTICAL INSTITUTION COURSE (PEC) USING MICROSOFT VISUAL BASIC 6.0. - Dodi Darmawan; Erik Orlando , SKom, MMSI (Jurnal Sistem Informasi, 2005)
In scientific writing, the writer explains the data processing application program design entrance test result in a special institution partical home course by using microsoft visual basic 6.0. this application program consists of six forms. and using program data access object for connection to the database. as well as using microsoft access 97 database.